Sosialisasi dan Pendampingan UMKM - Fitri Kurnia; Usmiar Usmiar; Ringgo Dinata; Nadya Syafitri (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
This socialization and mentoring is part of the Kuliah Kerja Nyata (KKN) activities for the Muhammadiyah University of West Sumatra students. This program is carried out as a form of concern for the community's economy. Socialization and assistance will be carried out on 19-20 September 2023, in Jorong Bumbun Aia, Tanjuang Bonai, Kec. Lintau Buo Utara, Kab. Tanah Datar. Activities are carried out semi-formally, in the form of visits to production sites. In this socialization and assistance, material related to business and MSMEs in general is delivered in language that is easy for business owners to understand. Business is not only about results but also planning, labor, promotion, and finance. Socialization and mentoring activities for MSMEs were carried out semi-formally and were welcomed by business owners.